Conducting Prolonged General Anesthesia without Intravenous Access in a Child with Hypoplastic Left Heart Syndrome. (17th October 2017) - Dang, Phat T.; Sriratana, Binjon
Abstract : Children with chronic medical conditions often need multiple intravenous (IV) access instances during their hospitalizations, both peripheral and central. Obtaining a working IV in this patient population undergoing general anesthesia can be challenging. In our case report, we describe a method of administering general anesthesia in an infant with partially repaired hypoplastic left heart syndrome without IV access.